Law Enforcement Of Fraud Through Electronic Media - I Nyoman Gede Sugiartha; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Fakultas Hukum, Universitas Warmadewa, 2021)
Fraud case of using electronic media often occur in Indonesia at the moment. This illustrates that the community is remain very vulnerable in carrying out activities related to the electronic media. For this reason, it is necessary to undertake a research regarding to criminal offenses using electronic means, especially against criminal fraud. This obsolutely obtains an attention to investigate about legal policies of fraud through electronic media, and criminal penalty of fraud perpetrators through Electronic Media. This study aims to find out about the criminal sanctions of fraud perpetrators through electronic media and to find out the legal policies of criminal acts of fraud through electronic media. This research used the Normative research method. Fraud in Indonesia as regulated in article 378 of the Criminal Code, while fraud by spreading false news which harms consumers in electronic transactions through online or electronic media is regulated in article 28 Paragraph (1) of the Information and Electronic Transaction Act. The spread of hoaxes is equated with acts of deception in the real world as stipulated in article 378 of the Criminal Code. Fraud criminal penalty through electronic media may be subject to multiple articles against a criminal act that fulfills the elements of a criminal offense as regulated in article 378 of the Criminal Code and meets the elements of a criminal act article 28 paragraph (1) of the Information and Electronic Transaction Act.